The elimination of human African trypanosomiasis: Monitoring progress towards the 2021–2030 WHO road map targets - Franco, Jose R.; Priotto, Gerardo; Paone, Massimo; Cecchi, Giuliano; Ebeja, Agustin Kadima; Simarro, Pere P.; Sankara, Dieudonne; Metwally, Samia B. A.; Argaw, Daniel Dagne (PLOS Neglected Tropical Diseases, 2024)
Author summary Human African trypanosomiasis (HAT), also known as “sleeping sickness, is a neglected tropical disease (NTD) transmitted by the bite of infected tsetse flies mainly affecting rural areas in sub-Saharan Africa. During the 20th century it caused enormous suffering in the endemic areas with a last reported peak in the late 1990s. This situation triggered a successful coordinated control effort that allowed, in 2012, the targeting of elimination of the disease as a public health problem by 2020. This paper follows previous papers to present the achievements towards HAT elimination. Annually reported cases have been kept below 1000 cases per year. HAT surveillance is maintained through active screening in endemic areas but also within a network of health facilities able to detect the disease. The World Health Organization (WHO), as defined in its 2021–2030 road map for NTDs, is now targeting the elimination of transmission of gambiense HAT and the elimination of rhodesiense HAT as a public health problem. The commitment of national health authorities and the international community will be essential to achieve these ambitious targets.